Factors Influencing MSMEs in Choosing Transactions in Sharia Financial Institutions and Its Impact on Increasing Income (Case Study of MSMEs Actors in Binjai, North Sumatera) - Olivia, Hastuti; Astuty, Widia; Sijauta, Dominggus; Radhiyah, Radhiyah; Yovi, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study is supposed to determine the factors that influence MSMEs’ choice to transact in Islamic Financial Institutions and their impact on increasing revenue. This type of research is quantitative research, this study uses an explanatory research approach. The population in this study is UMKM located in the city of Binjai who have never received capital financing from Islamic financial institutions and have a wage of Rp. 2,000,000 per month amounting to 270 people and the sample in this study using the Yamane Formula amounting to 73 respondents. Data analysis techniques in this study use the evaluation of the PLS-PM testing model on the outer test which aims to see the relationship between the indicators with the latent variables. The results of this study show, there are two factors that influence MSMEs in Binjai City to increase revenue by transacting in Islamic banking, the first is the factor of services provided by Islamic banking to customers (MSMEs) so that MSMEs know what products and services are available in Islamic banking then the second factor is financial literacy, currently, the financial literacy of MSMEs in Binjai City is still not optimal but little knowledge of Islamic banking products that are different from conventional banking and are able to help MSMEs in developing MSMEs businesses, with Islamic financial literacy, it is hoped that MSMEs will be able to get funding and the impact will result in an increase in the income of MSMEs themselves.